Letter (copy) : Hogar Espanol
001-0080-001 International. EAB/BT 12th March 1945. Mr. F. C. Woods, Clerical and Administrative Workers' Union, 30, Clouston Street, GLASGOW N.W. Dear Mr. Woods, HOGAR ESPANOL In reply to your letter of the 9th instant regarding the above matter, I have to inform you that a meeting of the International Committee will be held towards the end of this month, after which I will write you again. Yours sincerely, Secretary, International Department. 292/946/1/80